George Perry (1771–1823): architect and naturalist. Issue 1 (April 2022) - Leach, Stephen; Torrens, Hugh S.
Abstract : George Perry (1771–1823) was an artist, architect and sculptor, with a deep interest in natural history and malacology. (His father, George Perry ( c .1718–1771), was a pioneering industrialist, with a particular interest in geology and also the history of Liverpool.) He was the co-author (with John Corry) of The History of Liverpool (1807). He gave lectures on natural history and mineralogy and earned a living as an architect and sculptor. After bankruptcy in Liverpool in 1807, Perry re-established himself in London. There he published two books –  A descriptive catalogue of the pictures in the collection of the Marquis of Stafford in London (1807) and Conchology, or the natural history of shells (1811). He also published the serial publication entitled Arcana, or, the Museum of Natural History (1810–1811). After this, he disappeared from the public record until his death in Chelsea in 1823. His life and his contributions to natural history are summarized here.